STUDIES ON FOUNDATION HYBRIDS IN SILKWORM BOMBYX MORI L. - RAO, P. RAMA MOHANA; SINGH, RAVINDRA; NAGARAJ, C. S.; VIJAVARAGHAVAN, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
Improvement in foundation crosses over its pure parental strains in Chinese and Japanese type bivoltine silkworm was studied. Results indicate that larval duration was shorter in foundation crosses. Significant positive hybrid vigour was found in foundation crosses with regard to yield by number and by weight. There are specific advantages in rearing the foundation crosses than rearing the pure strains at the seed cocoon growers level.